1999
DOI: 10.1007/bf02482791
|View full text |Cite
|
Sign up to set email alerts
|

Generalized peritonitis with pneumoperitoneum caused by the spontaneous perforation of pyometra without malignancy: Report of a case

Abstract: Spontaneous perforation is a very rare complication of pyometra. We report herein the case of an 88-year-old woman who presented with muscular rigidity and free air on abdominal X-ray films. Perforation of the gastrointestinal tract was diagnosed preoperatively, and an emergency laparotomy was performed. A total hysterectomy with bilateral salpingo-oophorectomy was carried out under the diagnosis of generalized peritonitis caused by the spontaneous perforation of pyometra. The culture of purulent fluid from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Spontaneous perforation of a pyometra is an extremely rare complication. Only 16 cases have been reported so far and only one diagnosed preoperatively (5), which indicates the difficulty in giving a correct preoperative diagnosis of this disease. We report an elderly woman with generalized peritonitis and septic shock caused by spontaneous perforation of a pyometra diagnosed preoperatively during a computed tomography (CT) study.…”
mentioning
confidence: 82%
“…Spontaneous perforation of a pyometra is an extremely rare complication. Only 16 cases have been reported so far and only one diagnosed preoperatively (5), which indicates the difficulty in giving a correct preoperative diagnosis of this disease. We report an elderly woman with generalized peritonitis and septic shock caused by spontaneous perforation of a pyometra diagnosed preoperatively during a computed tomography (CT) study.…”
mentioning
confidence: 82%
“…The incidence of association with malignancy is reported to be 22-35% [7,20,24,27,38,39]. Since pyometra is caused by an impairment of the natural drainage of the cervix, it is likely to be associated with cervical, endometrial, or rectal or sigmoid colon cancer [7,20,24,27,38,39]. A pelvic examination should be performed to rule out associated malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as many patients with pyometra are asymptomatic [5], the diagnosis of pyometra is difficult. However, once pyometra perforation occurs, the pus spreads in the peritoneal cavity resulting in generalized peritonitis [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early reports on pyometra, most of the cases where caused by cervical occlusion due to malignant lesions [1]. However, recent reports have shown that the condition can also have benign causes [2]. Only approximately 22 cases have been reported in the English literature so far [3].…”
mentioning
confidence: 99%